Green poly(β-hydroxybutyrate)/starch nanocrystal composites: Tuning the nucleation and spherulite morphology through surface acetylation of starch nanocrystal. (1st September 2018) - Zhang, Guorui; Wu, Defeng; Xie, Wenyuan; Wang, Zhifeng; Xu, Chunjiang
Graphical abstract: Highlights: Pristine SNC is nucleating agent, while the acetylated SNC antinucleation one. Nucleating effect of pristine SNC results in shortening of lamellar twist period. Repulsive effect of acetylated SNC aggravates degradation of banded structure. This work provides new way to control PHB spherulite morphology using SNC. Abstract: Starch nanocrystal (SNC) particles were used as the filler to prepare green composites with biodegradable poly(β-hydroxybutyrate) (PHB). An interesting way to tune the nucleation and banded morphology of composites by the surface acetylation of SNC was proposed. Pristine SNC acts as the nucleating agent, while acetylated SNC as the antinucleation one to PHB. This role switching is due to improved polymer-particle compatibility after surface acetylation of SNC particles. The banded structure of PHB spherulites degrades evidently in the presence of two kinds of SNC particles, showing decreased ring-band space, with deteriorated periodicity and increased flocculation of peak-to-valley height. But the two kinds of composites have different mechanisms on the degradation of their ring-bands because the two kinds of SNC particles, pristine SNC and acetylated one, have different influences on the PHB spherulite growth rates and system undercooling. This work also opens a new window for the applications of SNC particles.